Purinergic Receptors: Key Mediators of HIV-1 Infection and Inflammation - Swartz, Talia H.; Dubyak, George R.; Chen, Benjamin K. (Frontiers in Immunology, 2015)
Human immunodeficiency virus (HIV-1) causes a chronic infection that afflicts more than 38 million individuals worldwide. While the infection can be suppressed with potent anti-retroviral therapies, individuals infected with HIV have elevated levels of inflammation as indicated by increased T cell activation, soluble biomarkers, and associated morbidity and mortality. A single mechanism linking HIV pathogenesis to this inflammation has yet to be identified. Purinergic receptors are known to mediate inflammation and have been shown to be required for HIV-1 infection at the level of HIV-1 membrane fusion. Here we review the literature on the role of purinergic receptors in HIV-1 infection and associated inflammation and describe a role for these receptors as potential therapeutic targets.